Identification of the ancestral killer immunoglobulin-like receptor gene in primates - Coggill Penny; Vernikos George S; Piatak Mike; Andersen Hanne; Bashirova Arman; Sambrook Jennifer G; Lifson Jeff D; Carrington Mary; Beck Stephan (BMC Genomics, 2006)
Abstract Background Killer Immunoglobulin-like Receptors (KIR) are essential immuno-surveillance molecules. They are expressed on natural killer and T cells, and interact with human leukocyte antigens. KIR genes are highly polymorphic and contribute vital variability to our immune system. Numerous KIR genes, belonging to five distinct lineages, have been identified in all primates examined thus far and shown to be rapidly evolving. Since few KIR remain orthologous between species, with only one of them, KIR2DL4, shown to be common to human, apes and monkeys, the evolution of the KIR gene family in primates remains unclear. Results Using comparative analyses, we have identified the ancestral KIR lineage (provisionally named KIR3DL0) in primates. We show KIR3DL0 to be highly conserved with the identification of orthologues in human (Homo sapiens), common chimpanzee (Pan troglodytes), gorilla (Gorilla gorilla), rhesus monkey (Macaca mulatta) and common marmoset (Callithrix jacchus). We predict KIR3DL0 to encode a functional molecule in all primates by demonstrating expression in human, chimpanzee and rhesus monkey. Using the rhesus monkey as a model, we further show the expression profile to be typical of KIR by quantitative measurement of KIR3DL0 from an enriched population of natural killer cells. Conclusion One reason why KIR3DL0 may have escaped discovery for so long is that, in human, it maps in between two related leukocyte immunoglobulin-like receptor clusters outside the known KIR gene cluster on Chromosome 19. Based on genomic, cDNA, expression and phylogenetic data, we report a novel lineage of immunoglobulin receptors belonging to the KIR family, which is highly conserved throughout 50 million years of primate evolution.